'It is home but it is not home': habitus, field and the migrant. (June 2013) - Noble, Greg
This article explores the utility of Bourdieu's notions of habitus and field in examining the experience of migrant resettlement. It draws on a speech spoken in two languages at a community organisation event to suggest that resettlement entails the transformation of the embodied capacities of migrants and the formation of a new set of bodily capacities which never quite become the dispositions of the citizen who 'belongs' unconditionally. It argues that, through a process of disorientation and reorientation, some migrants acquire a corporeal and social awkwardness which embodies the learning of the 'difference of difference'. This differentiation is less about personal experience than social location, and it is less about some primordial 'ethnicity' deriving from the homeland than an 'ethnicised' habitus that reflects that location within Australian social fields. The article challenges Bourdieu's insistence on the complicit relation between habitus and field, arguing that we need to draw on a micro-sociological language of 'settings' to account for migrants' experiences of moving across and switching between social fields.